Pengaruh Penerimaan Dana ZISWAF, NPF Gross, dan Pendapatan Mudharabah terhadap ROE Dengan Firm Size sebagai Variabel Moderasi pada Perbankan Syariah di Indonesia Periode 2018 Q1-2023 Q3. - Firdaus, Violinda Syahgaria; Budianto, Eka Wahyu Hestya (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Syekh Wasil Kediri, 2024)
This research aims to analyze the effect of receiving Zakat, Infaq, Alms, and Waqf (ZISWAF), Gross Non-Performing Financing (NPF), and Mudharabah Income on Return on Equity (ROE) with Firm Size as a moderation variable in Islamic Banking in Indonesia during the period 2018.Q1 to 2023.Q3. The sampling technique used was purposive sampling, with a total sample of 115 companies for 5 years. The data analysis techniques used are Panel Data Regression Analysis and Moderated Regression Analysis (MRA) with the Eviews 12 application. The results showed that the receipt of ZISWAF funds had a significant negative effect on ROE in the financial sector for the period 2018.Q1-2023. Q3. Gross NPF has a significant negative effect on ROE in the financial sector for the period 2018.Q1-2023. Q3. Mudharabah revenue has a significant negative impact on ROE in the financial sector for the period 2018.Q1-2023. Q3. Firm Size is able to moderate the effect of receiving ZISWAF funds on ROE in the financial sector for the 2018.Q1-2023 period. Q3. Firm Size is able to moderate the influence of NPF Gross on ROE in the financial sector for the period 2018.Q1-2023. Q3. Firm Size is able to moderate the effect of mudharabah income on ROE in the financial sector for the 2018.Q1-2023 period. Q3.